PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA WORDWALL SUB TEMA HIDUP SEHAT TERHADAP HASIL BELAJAR SISWA KELAS 3 DI SEKOLAH DASAR NEGERI 1 PEMARON (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This study aims to determine the effect of implementing the Wordwall assisted Problem Based Learning (PBL) model on the learning outcomes of third grade students at SD Negeri 1 Pemaron on the sub theme of “Healthy Living.” The method used was a quasi experiment with a non equivalent control group design, in volving an experimental class that received PBL assisted by Wordwall and a control class with conventional learning. Data were collected through multiple choice objective tests and analyzed using normality, homogeneity, and t-tests. The results of the study indicate that the application of PBL assisted by Wordwall significantly improves student learning outcomes compared to conventional methods. These findings show that the integration of problem based learning models with interactive media can increase student engagement, critical thinking skills, and conceptual understanding. This study provides practical contributions for teachers and schools in improving the quality of thematic learning through technology.